Respuesta :
Because [tex]f,g[/tex] are continuous,
[tex]\displaystyle\lim_{x\to3}(2f(x)-g(x))=2\lim_{x\to3}f(x)-\lim_{x\to3}g(x)=2f(3)-g(3)=4[/tex]
[tex]10-g(3)=4[/tex]
[tex]g(3)=6[/tex]
[tex]\displaystyle\lim_{x\to3}(2f(x)-g(x))=2\lim_{x\to3}f(x)-\lim_{x\to3}g(x)=2f(3)-g(3)=4[/tex]
[tex]10-g(3)=4[/tex]
[tex]g(3)=6[/tex]
The value of g(3) using the limit is 6
Given :
f and g are continuous functions with f(3)=5
[tex]\lim_{n \to 3} [2f(x)-g(x)]=4[/tex]
From the given limit function we replace f(3) by 5
also we replace all x by 3 to find the limit
[tex]\lim_{n \to 3} [2f(x)-g(x)]=4\\ 2f(3)-g(3)=4\\2(5)-g(3)=4\\10-g(3)=4\\-g(3)=4-10\\-g(3)=-6\\g(3)=6\\[/tex]
So the value of g(3)=6
Learn more : brainly.com/question/1602360